High-Definition Transcranial Direct Current Stimulation Over the Right Lateral Prefrontal Cortex Increases Maximization Tendencies - Wang, Haixia; Zhang, Hanqi (Frontiers in Behavioral Neuroscience, 2021)
People seek the best in every aspect of life. However, little is known about the neurobiological mechanisms supporting this process of maximization. In this study, maximization tendencies were increased by using high-definition transcranial direct current stimulation (HD-tDCS) over the right dorsolateral prefrontal cortex (DLPFC). Participants (n = 64) received 2 mA anodal 4 × 1 HD-tDCS or sham stimulation over the right DLPFC in two sessions and subsequently completed an N-back working memory task and a maximization scale (MS). We observed that maximization tendency scores increased during anodal stimulation. Furthermore, the results indicate that this increase in maximization tendency was driven by motivational changes. On the MS, alternative search subscale scores were significantly increased, demonstrating an increase in motivation to evaluate more alternatives; however, the results did not indicate that the increase in maximization tendencies was due to working memory improvement. These results demonstrated that maximization tendencies can be strengthened through noninvasive interventions and that the right DLPFC has a causal relationship with maximization tendencies.